Peningkatan Hasil Belajar Pendidikan Pancasila Terintegrasi Literasi dan Numerasi Melalui Model Problem Based Learning (PBL) di Kelas 2 SD Tambakrejo 01 - Wijayanti, Istiana; Ida Dwijayanti; Aries Tika Damayani; Ika Susianingsih (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This study aims to improve the learning outcomes of Pancasila Education integrated with literacy and numeracy through the application of the Problem Based Learning (PBL) model in grade 2 students of Tambakrejo 01 Elementary School. This classroom action research was conducted in three cycles with stages of planning, implementation, observation, and reflection. The subjects of the study were 27 grade 2 students. The data collection technique used tests. The results of the study showed a significant increase in the learning outcomes of Pancasila Education integrated with literacy and numeracy after the application of the PBL model. This increase can be seen from the average student scores which increased in each cycle as well as the increase in student involvement and motivation to learn. Thus, the Problem Based Learning model is effective for improving the learning outcomes of Pancasila Education integrated with literacy and numeracy in grade 2 of Tambakrejo 01 Elementary School.